Pretreatment plasma HGF as potential biomarker for susceptibility to radiation-induced liver dysfunction after radiotherapy. Issue 1 (December 2018) - Hong, Theodore; Grassberger, Clemens; Yeap, Beow; Jiang, Wenqing; Wo, Jennifer; Goyal, Lipika; Clark, Jeffrey; Crane, Christopher; Koay, Eugene; Dima, Simona; Eyler, Christine; Popescu, Irinel; et al.
Abstract Radiotherapy shows excellent local control in liver cancers but carries the risk of radiation-induced liver dysfunction and liver failure. We conducted a study of plasma hepatocyte growth factor (HGF) in a clinical trial of proton radiotherapy in patients with unresectable liver cancers (NCT00976898), and in an observational study for liver cancer patients undergoing surgical treatments. Liver dysfunction within 3 months after radiotherapy—a Childs−Turcotte−Pugh (CTP) score increase of 1 point or more—occurred in 9/34 (26%) of patients. Patients with no increase in CTP score had lower pretreatment plasma HGF level (p  = 0.015). Both the increase in CTP score (p  = 0.034) and the pretreatment plasma HGF (p  = 0.017) were associated with OS. Plasma HGF was significantly associated with presence of cirrhosis (p  = 0.0027) and with Model for End-stage Liver Disease (MELD) score (p  < 0.0001), but not with OS in surgical liver cancer patients. Pretreatment plasma HGF is a candidate biomarker for patient selection for radiotherapy.